2022
DOI: 10.3390/toxics11010024
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Diclofenac Sodium by Aged Degradable and Non-Degradable Microplastics: Environmental Effects, Adsorption Mechanisms

Abstract: Microplastics (MPs) are novel pollutants, which can carry toxic contaminants and are released in biota and accumulate. The adsorption behavior of MPs and aged MPs has attracted extensive attention. In this paper, the aging process of polystyrene (PS) and poly (butyleneadipate-co-terephthalate) (PBAT) plastics under ultraviolet (UV) irradiation at a high temperature and their adsorption properties for the contaminant diclofenac sodium (DCF) before and after aging was investigated. There are many factors affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…value, i.e., a higher content of carbonyl and carboxyl groups, compared to its pristine analogue. A similar case was reported in the study by Liang et al [53], which demonstrated the adsorption of DCF on UV-aged poly(butylene adipateco-terephthalate)-PBAT. The particle size of PBAT ranged from 75 to 150 µm, while aged samples showed a decrease in crystallinity and an increase in the oxygen-containing group, as well as a decrease in hydrophobicity.…”
Section: Influence Of Key Parameters On Adsorption Of Dcf On Pristine...supporting
confidence: 85%
See 1 more Smart Citation
“…value, i.e., a higher content of carbonyl and carboxyl groups, compared to its pristine analogue. A similar case was reported in the study by Liang et al [53], which demonstrated the adsorption of DCF on UV-aged poly(butylene adipateco-terephthalate)-PBAT. The particle size of PBAT ranged from 75 to 150 µm, while aged samples showed a decrease in crystallinity and an increase in the oxygen-containing group, as well as a decrease in hydrophobicity.…”
Section: Influence Of Key Parameters On Adsorption Of Dcf On Pristine...supporting
confidence: 85%
“…Therefore, they suggested that the interactions were hydrophobic interactions, focusing on the hydrogen–halogen bonds formed between the nitrogen, oxygen, and chlorine atoms on DCF and the hydrogen atoms on MPs. Additionally, electrostatic interactions were suggested due to the surface charge of PBAT MPs and the ionic form of DCF at the optimal acidic pH conditions in their case, as well as π–π stacking due to the fact that both DCF and PBAT MPs have and share an affinity with aromatic rings [ 53 ]. Accordingly, the analogy with our study can be drawn to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Narkis and Sun et al have reported surfactant concentrations ranging from several hundred to several thousand mg L –1 in industrial wastewater. , The structures of surfactants encompass copious oxygen-containing functional groups capable of modifying the sorption behavior and migration of pollutants on MPs . MPs, being hydrophobic organic pollutants, transform their physicochemical properties upon the introduction of surfactants, subsequently influencing their sorption characteristics in conjunction with other pollutants. Understanding the impact of chemical surfactants on the behavior of MPs within the environment assumes paramount significance. Alas, investigations into the sorption effects of MPs in the presence of chemical surfactants remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“… 20 MPs, being hydrophobic organic pollutants, transform their physicochemical properties upon the introduction of surfactants, subsequently influencing their sorption characteristics in conjunction with other pollutants. 21 23 Understanding the impact of chemical surfactants on the behavior of MPs within the environment assumes paramount significance. Alas, investigations into the sorption effects of MPs in the presence of chemical surfactants remain scarce.…”
Section: Introductionmentioning
confidence: 99%